Temporal and Spatial Changes in Crop Patterns, Use of Inputs and Hydrological Alteration in the Case of Fogera Floodplain, Ethiopia - Mare Addis Desta; Gete Zeleke; William A. Payne; Wubneh Belete Abebe (Ecologies, 2021)
More than half of the world’s population consumes rice. Recently, the area sown with modern rice varieties has expanded, and the use of chemical fertilizers and pesticides has increased in various countries. Wetland hydrology is also influenced by chemical and physical characteristics. Hence, this research focused on temporal and spatial changes in crop patterns, input usage, and hydrology in the Ethiopian Fogera floodplain, with the following objectives: (a) What are the spatial and temporal trends in crop production patterns? (b) What input changes have occurred to produce rice and other crops? (c) What hydrological changes have occurred in the area with intensification of production systems? Primary data were gathered through a questionnaire, focus group discussions, interviews, and field observations. Secondary data were obtained from Landsat imageries, the SWAT model, water flow measurements, and normalized difference vegetation index (NDVI). NDVI results indicated that the area cultivated for rice is increasing while the area of other crops is decreasing. Agricultural inputs are used in rice systems but were not used before the introduction of rice. Recession farming activities have also diminished wetland areas. Water flow showed a decrease, whereas Nitrogen and Phosphorus showed an increase with Pearson’s correlation values −0.069 and −0.072, respectively. Flow of water was negatively correlated with N and P water concentration, whereas N and P contents were positively correlated. In conclusion, growth of intensive rice systems has had negative environmental consequences on wetland ecology. Therefore, policies to regulate and manage wetland uses are recommended.